Examining the Product Adoption Rates and Viability of Mobile Health Microinsurance in Zimbabwe. - Manyima Rudo Matsika; Mutanga Marcus (Indian Journals, 2023)
The study sought to evaluate the product adoption rates and viability of mobile health microinsurance in Zimbabwe. The main objectives were to examine the potential benefits of mobile health microinsurance to the poor and the insurers; assess the challenges of mobile health microinsurance to the insurers and insureds; examine the product uptake rates of mobile health micro insurance and assess the viability of mobile health microinsurance in Zimbabwe. The study adopted the explanatory and descriptive research design. The research focused on the company that is currently offering the mobile health microinsurance product as well as clients who are currently insured under the product which is the Hospital Cash Plan. A total of 50 respondents was used (comprising of 10 executives and 40 walk in clients) as study subjects. Questionnaires and interviews were used as research instruments to collect data. The research findings revealed that the adoption rates are low and the scheme had not been performing well. The mobile health microinsurance products need to reach large volumes and be correctly priced in order to be viable and profitable. Insurers highlighted challenges of lack of awareness and education by clients as causing the low rates. The study recommended use of advertisement of the products their products, correct pricing, strategic alliances with NGOs, coming up with innovative products, fewer exclusions to attract more clients and educational awareness.